PRODUKTIVITAS ALAT BERAT DAN BIAYA PELAKSANAAN PEKERJAAN PADA PROYEK PEMELIHARAAN BERKALA RUAS JALAN: SUNGAI LAKUM – PASAR KAMIS (KERTAK HANYAR) - Aulia Isramaulana; Rizka Norjanah (INFO-TEKNIK, 2020)
On the project Periodic Maintenance of Road Sungai Lakum Pasar Kamis is a project implemented using heavy equipment. By using heavy equipment, will facilitate and accelerate the course of the project. The tools used must be considered maintenance, because it is very influential on the production tools and costs incurred for the use of the tool. This study aims to analyze the use of heavy equipment in the periodic Maintenance Project of road Sungai Lakum Pasar Kamis by using theoretical analysis based on field data. Analyzing the calculation is the productivity and cost of the equipment on the scope of work that is the work of the land, widening work and road shoulder work, grinding pavement work, and asphalt work, using Excel program as a tool in data processing so that the achievement of the use of heavy equipment available in finish the job. Based on the calculation obtained the price of theoretical analysis unit based on field data for the work of preferred stockpiles from the source of Rp. 310.994.714,2; Class B aggregate base layer Rp. 76.127.086,04; Aggregate base layer with hill excavation Rp. 59.705.050,39; Class A base aggregate layer Rp. 204.703.029,9; Asphalt lining resap coat liquid Rp. 3.038.436,28; Lataston coating foundation Rp. 306.997.682,6. Where the calculation of unit price based on field data is smaller than the unit price of the bid data.